Handbook of big data - Bühlmann, Peter; Drineas, Petros; Kane, Michael; Laan, M. J. van der (Chapman & Hall/CRC handbooks of modern statistical methods)
"Handbook of Big Data provides a state-of-the-art overview of the analysis of large-scale datasets. Featuring contributions from well-known experts in statistics and computer science, this handbook presents a carefully curated collection of techniques from both industry and academia. Thus, the text instills a working understanding of key statistical and computing ideas that can be readily applied in research and practice"--